Pengembangan Media Virtual Tour Gedung Teaching Factory Politeknik Negeri Batam - Ika Juniar Kristiani; Riwinoto Riwinoto; Muhammad Ersandi Mangaraja (JOURNAL OF APPLIED MULTIMEDIA AND NETWORKING, 2020)
Virtual reality is currently growing rapidly; a variety of industrial products have emerged that are integrated with the virtual world in various sectors. Since 2018, the virtual laboratory of the Batam State Polytechnic has developed learning products that support virtual reality technology. These learning products are in the form of games and learning simulations. It is expected that through the learning products produced, the learning activities will be more targeted and the effectiveness of lectures will increase. Virtual touring is one of the benefits of virtual reality technology. In the tourism sector, many virtual touring media have been developed that are useful in the introduction and promotion of local tourism place. Adopting the advantages and benefits of virtual tours in the tourism sector, the education sector has also developed many virtual tour media that are useful in introducing related educational institutions or institutions. These benefits will be developed by Batam State Polytechnic to introduce one of the Lecture Buildings, the Teaching Factory. This virtual tour media will be addressed to Batam State Polytechnic guests who come to visit to introduce virtual laboratory facilities and students who need information on the location and condition of the Batam State Polytechnic Teaching Factory Building.